Faecal microbiota in dogs with multicentric lymphoma. (20th November 2017) - Gavazza, A.; Rossi, G.; Lubas, G.; Cerquetella, M.; Minamoto, Y.; Suchodolski, J. S.
Abstract : Malignant lymphoma B‐cell type is the most common canine haematopoietic malignancy. Changes in intestinal microbiota have been implicated in few types of cancer in humans. The aim of this prospective and case‐control study was to determine differences in faecal microbiota between healthy control dogs and dogs with multicentric lymphoma. Twelve dogs affected by multicentric, B‐cell, stage III‐IV lymphoma, and 21 healthy dogs were enrolled in the study. For each dog, faecal samples were analysed by Illumina sequencing of 16S rRNA genes and quantitative PCR (qPCR) for selected bacterial groups. Alpha diversity was significant lower in lymphoma dogs. Principal coordinate analysis plots showed different microbial clustering ( P = .001) and linear discriminant analysis effect size revealed 28 differentially abundant bacterial groups in lymphoma and control dogs. The qPCR analysis showed significant lower abundance of Faecalibacterium spp. ( q < .001), Fusobacterium spp. ( q = .032), and Turicibacter spp. ( q = .043) in dogs with lymphoma compared with control dogs. On the contrary, Streptococcus spp. was significantly higher in dogs with lymphoma ( q = .041). The dysbiosis index was significantly higher ( P < .0001) in dogs with lymphoma. In conclusion, both sequencing and qPCR analyses provided a global overview of faecal microbial communities and showed significant differences in the microbial communities of dogs presenting with multicentric lymphoma compared with healthy control dogs.